The evaluation of strengthening effect reinforced concrete structures with FRP on seismic dynamic performance of the structures - Mohammad Kazem Sharbatdar (Iranian Society of Structrual Engineering (ISSE), 2019)
Nowadays, Strengthening of existing structures was conducted by FRP wrapping in Iran in order to increase capacity and ductility particularly for columns resulting in an increase in the strength of concrete and improve structure behaviour. In this study, RC strengthened (with FRP) and un-strengthened buildings with 3, 5, 10 & 15 stories and 1 to 5 bay were considered. By performing linear and non-linear static analyses, seismic parameters such as acceleration and spectral displacement, damping and effective period of structure in performance points and capacity curves were discussed. The results indicated that the confinement of beams and columns of RC structures with CFRP sheets will improve the absorption and dissipation energy of structure and the stiffness and initial gradient of retrofitted structure with CFRP were about 1.5 to 2.5 times of those of original un-strengthened structure. And also via strengthening of structure with CFRP sheets, the spectral acceleration was increased and the spectral displacement, damping ratio and effective period were decreased, resulting in increasing seismic loading capacity. However, the structure retrofitted by CFRP with 3-stories, 4 bays showed the best performance in the term of stiffness, more spectral acceleration and spectral displacement and less effective period, but in the term of damping and energy absorption the best performance was for the structure with 10-stories, 4 bays.